(untitled) (Ustozlar uchun, 2024)
Annotation: This article delves into the initiatives undertaken by the World Bank to foster digital economy development across the globe. It provides an overview of the literature surrounding digital economy support projects, examines the methodologies employed by the World Bank, presents the results achieved, discusses the implications, and offers suggestions for future endeavors.